Polarization dependence of molecular adsorption on ferroelectrics. (24th March 2013) - Kraya, Laura Y.; Kraya, Ramsey
<x xml:space="preserve">Abstract</x> The structural details of ferroelectric surfaces influence the effect of ferroelectric polarization on surface chemistry, and it is important to understand and control defect functionality as well as identify adsorption sites in ferroelectric materials. Ferroelectric domain polarization has been found to have a significant effect on surface properties and interactions. Here, both the structure and the presence of local electric fields are examined simultaneously. The surface structure and ferroelectric domain orientation are controlled while molecular adsorption effects are quantified. We use scanning tunneling microscopy (STM) to determine the surface and electronic effects of polarization–gas interactions on a model ferroelectric surface, BaTiO3 (001).